Inequality and growth: A review on a great open debate in economics - Enea Baselgia; Reto Foellmi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
What is the relationship between inequality and growth? This question has occupied and fascinated social scientists for more than a century. This article critically reviews the recent empirical and theoretical literature on the complex interplay between inequality and economic growth. Inequality might come in many forms: (top) incomes, wages, wealth, land, or opportunities. At the same time, growth performance could be measured as average growth rates, variability of growth, or the potential for growth to 'take off'. We consider causality running from inequality to growth; hence, the Kuznets hypothesis is only touched on in passing. The empirical literature estimating the effect of inequality on growth has produced a wide range of results, precluding clear-cut conclusions on the inequality-growth relationship. Consequently, it remains central to understand the underlying economic causes and channels through which (different aspects of) inequality can promote or hamper economic growth. This review aims to provide a broad overview of the contemporary results and an outline for prospective empirical and theoretical work.
Keywords: D30; O10; O31; O40; 330; economic growth; inequality; redistribution; theory and evidence